Impacts of the COVID-19-driven rise in global rice prices on consumers in Papua New Guinea - Schmidt, Emily; Dorosh, Paul A. (International Food Policy Research Institute, 2022)
During the early months of the COVID-19 pandemic, several major rice exporting countries, grappling with rising economic uncertainties, suspended rice exports to ensure adequate domestic supply. Viet Nam, Cambodia, and Myanmar temporarily halted rice exports, contributing to spikes in rice prices on international markets. By April 2020, rice prices had increased by over 35 percent in Thailand and 20 percent in Viet Nam (important benchmark countries for international rice price monitoring). International rice prices rose an average of 25 percent during March–September 2020 and remained high (on average 36 percent higher in March 2021) compared to pre-COVID-19 levels, despite the loosening of rice export restrictions and quarantine measures in the second half of 2020.